Epilepsy Is Associated With Dysregulation of Long Non-coding RNAs in the Peripheral Blood - Hashemian, Fatemeh; Ghafouri-Fard, Soudeh; Arsang-Jang, Shahram; Mirzajani, Sara; Fallah, Hamid; Mehvari Habibabadi, Jafar; Sayad, Arezou; Taheri, Mohammad (Frontiers in Molecular Biosciences, 2019)
Background: Long non-coding RNAs (lncRNAs) are a group of functional transcripts that are not translated to proteins. Recent investigations have underscored their role in the pathogenesis of neurodevelopmental disorders. Methods: In the current investigation, we quantified expression levels of four lncRNAs (HOXA-AS2, SPRY4-IT1, MEG3 and LINC-ROR) in peripheral blood of epileptic patients and normal controls. Results: Expression of HOXA-AS2 was significantly higher in patients compared with controls (Posterior beta=1.982, P value=0.001). We detected interaction effects of gender on expression of HOXA-AS2 (P value=0.012). Further analyses showed over-expression of HOXA-AS2 in male patients compared with male controls (P value=0.003), in spite of similar levels of expression between female cases and female controls (P value=0.77). Expression of SPRY4-IT1 was higher in total patients compared with total controls (Posterior beta=1.27, P value=0.02). Such difference was only observed between male patients and male controls when dividing study participants based on their gender (P value=0.012). There was no significant difference in expression of MEG3 and LINC-ROR between patients and controls. Conclusion: Expression levels of all lncRNAs were correlated with each other with r values ranging from 0.61 to 0.76 (P values<0.0001). However, expressions of none of lncRNAs were correlated with age of study participants. The current data implies a putative role for two lncRNAs in the pathogenesis of epilepsy and warrants future functional studies to verify the observed association.